A Bioconjugate Vaccine Against Extra-Intestinal Pathogenic Escherichia coli (ExPEC) - Linhui Hao; Wenhua Huang; Yan Guo; Xiankai Liu; Jun Wu; Li Zhu; Chao Pan; Hengliang Wang (Vaccines)
Background: Extra-intestinal pathogenic Escherichia coli (ExPEC) represents a major global public health challenge due to its ability to cause diverse clinical infections, including urinary tract infections, bacteremia, neonatal meningitis, and sepsis. The growing prevalence of multidrug-resistant (MDR) ExPEC strains, which rapidly erode antibiotic efficacy, underscores vaccine development as a critical priority. Bioconjugate vaccines have emerged as a promising approach to mitigate ExPEC-associated infections. Methods and Results: In this study, we utilized protein glycan coupling technology (PGCT) based on oligosaccharyltransferase (OST) PglL to engineer a tetravalent bioconjugate vaccine targeting four predominant ExPEC serotypes (O1, O2, O6, and O25). We conducted a series of experiments to demonstrate the efficacy of the conjugate vaccine in eliciting humoral immune responses and inducing the production of specific antibodies against Escherichia coli O1, O2, O6, or O25 serotypes. Conclusions: This work establishes the first application of the O-linked PGCT system for engineering bioconjugate vaccines against ExPEC infections.